Annual Plan 1973-74 - Planning Commission (Planning Commission, 1973)
The Annual Plan for 1973-74 has been formulated keeping in view the basic objective of accelerated economic growth in a frame-work of greater social justice and economic self-reliance. The translation of the concept of self-reliance into one of reality calls for massive increase in our exports coupled with adequate expansion of such vital import substitutes as iron and steel, fertilisers, petroleum and non-ferrous metals. Considerable stress has, therefore, been laid in the Annual Plan for accelerating development in these areas. Of the total outlay provided under the head “Industry and Minerals’’ in the Central sector, 28% is allocated for steel, 13% for fertilisers, 10% for petroleum and 9% for non-ferrous metals.
Government of India Planning Commission
Government of India Planning Commission